2022
DOI: 10.3390/agronomy12071558
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Phosphorus Use in Sunflower

Abstract: Sunflower is an oleaginous plant of great importance worldwide that stands out in the production of edible oil and human food. The identification of differences between cultivars regarding the use of phosphorus and the production of achenes at different levels of phosphate fertilization is a viable strategy to allow its cultivation in soils with different concentrations of phosphorus, without compromising yield and reducing environmental damage associated with excessive applications of phosphate fertilizers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…The implication of this finding is that soil testing, soil fertility management and improvement could be used as a strategy for increasing hybrid sunflower productivity in northern Uganda. Oliveira et al (2022) described the benefits of Phosphorus fertilization for sunflower. Other studies have also shown that phosphorus application promotes growth and increases sunflower yield (Abaca et al, 2022;Sadozai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The implication of this finding is that soil testing, soil fertility management and improvement could be used as a strategy for increasing hybrid sunflower productivity in northern Uganda. Oliveira et al (2022) described the benefits of Phosphorus fertilization for sunflower. Other studies have also shown that phosphorus application promotes growth and increases sunflower yield (Abaca et al, 2022;Sadozai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, farmers have initiated to utilize of organic fertilizers to improve soil chemical and physical structure. Crop productivity is increased by carefully adjusting agricultural methods such as fertilization, tillage, and removal of weeds [14][15][16][17]. There are several kinds of organic fertilizers, such as biofertilizers which are considered the most recent eco-friendly technique for promoting sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Para tanto são realizados ensaios em diferentes ambientes para determinação do comportamento agronômico dos genótipos de girassol disponíveis e sua capacidade de adaptação (TARSITANO et al 2016). Tais variedades podem apresentar diferentes características em relação à altura de plantas, área foliar, tamanho de capítulo, resposta à adubação, resistência a pragas e doenças, dentre outras (MARCHESINI et al 2018, TAHA et al 2018, SOARES et al 2020, OLIVEIRA et al 2022). Estas variações podem ter um efeito direto na interação da planta com as condições de cultivo, em especial a densidade de plantas utilizada na implantação da lavoura (SILVA & ALMEIDA 1994).…”
Section: Introductionunclassified